Dysregulated Th1 cells in lung squamous cell carcinoma. Issue 6 (10th June 2022) - Wang, Jiahui; Zhou, Jian; Zhou, Qiuru; Qi, Ying; Zhang, Peng; Yan, Cihui; Ren, Xiubao
Abstract: Lung squamous cell carcinoma (LUSC) is a common subtype of lung cancer. Th1 cells contribute to antitumor immune responses. However, there are few studies on Th1 cells in LUSC. CD8 + T cells are the main driver of the antitumor immunity, targeting tumor cells killing. Th1 cells play an important auxiliary role in this process. Here, we used single-cell RNA-seq (scRNA-seq) to analyze qualified CD4 + T cells and Th1 cells (defined CD4 + T cells with 1 or more of STAT1 +, STAT4 +, T-bet +, and IFN-γ + as Th1 cells) from tissues of 8 LUSC patients. Then, we validated Th1 cells and CD8 + T cells of 32 LUSC patients by multiplex immunofluorescence staining and immunohistochemistry. Finally, we used flow cytometry to detect IFN-γ of CD4 + T cells in human PBMCs coincubated with LUSC-derived supernatant to simulate a tumor inhibitory microenvironment. ScRNA-seq showed IFN-γ + Th1 cells account for 25.28% of all Th1 cells. Gene ontology and Kyoto encyclopedia of genes and genomes (KEGG) pathway enrichment analyses of differentially expressed genes between IFN-γ + Th1 cells and IFN-γ – Th1 cells confirmed the decreased IFN-γ is associated with endoplasmic reticulum stress (ER stress). Multiplex immunofluorescence staining and immunohistochemistry proved there was a positive correlation between IFN-γ + STAT1 + T-bet + Th1 cells and CD8 + T cells. Flow cytometry showed IFN-γ secreted by Th1 cells is decreased. These findings support the claim that Th1 cells' function is suppressed in LUSC. Through scRNA-seq, we found that the decreased Th1 cells' function is associated with ER stress, which requires further study. Overall, these findings may produce a new method for the treatment of LUSC. Graphical Abstract: Th1 cells' function is suppressed in LUSC. Through scRNA-seq, the decreased Th1 cells' function is associated with ER stress, which requires further study.